250+14h=22h

Simple and best practice solution for 250+14h=22h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 250+14h=22h equation:


Simplifying
250 + 14h = 22h

Solving
250 + 14h = 22h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-22h' to each side of the equation.
250 + 14h + -22h = 22h + -22h

Combine like terms: 14h + -22h = -8h
250 + -8h = 22h + -22h

Combine like terms: 22h + -22h = 0
250 + -8h = 0

Add '-250' to each side of the equation.
250 + -250 + -8h = 0 + -250

Combine like terms: 250 + -250 = 0
0 + -8h = 0 + -250
-8h = 0 + -250

Combine like terms: 0 + -250 = -250
-8h = -250

Divide each side by '-8'.
h = 31.25

Simplifying
h = 31.25

See similar equations:

| 3=5x+12 | | t+(2t+4)=-5 | | 8x/3-5x/4=-13 | | 5/25=y/85 | | -(5b+5)-5=1-(5b-1) | | -36=4w | | 11=3-7x | | X^3-2X+0.5=0 | | X^3-2X-0.5=0 | | 22=2c | | -2(2(2)-4)=-4(-2+2) | | 4x^2+9x-2=0 | | .90x+.52(2-x)=.10(-118) | | 3x-16cm=200cm | | 7x+2[3(1-x)]=14 | | 3(t+2)-(3t-3)=2(3t-4)-13 | | 3(t+2)-(3t-3)=2 | | 64=8n | | (x+3)-2c-(1-3x)=2 | | 6w^3-28w+16=0 | | .5y+2=.8y-.3 | | x=4x+96 | | 2w-6m=50m | | -8(-1)-(3(-1)+6)=4+-1 | | -7=3(x-5)-x | | x-13x+10x=50-6 | | -17+2x=6-x | | X=10+-2X | | (x+1)(x+2)=2x | | 6x+14=2x | | 0.25(q-12)=4 | | 10n=4n+5+5n |

Equations solver categories